Europe: so many languages, so many cultures - Steinhauer, Hein (UI Scholars Hub, 2011)
The number of different languages in Europe by far exceeds the number of countries. All European countries have national languages, and in nearly all of them there are minority languages as well, whereas all major languages have dialects. National borders rarely coincide with linguistic borders, but the latter (including dialect borders) mark by their nature also more or less distinct cultural areas. This paper presents a survey of the different language families represented in Europe: Indo-European, Uralic, Altaic, and the four Caucasian language families, each with their sub-branches and individual languages. Some information is given on characteristic structural phenomena and on the status and history of these languages or language families and on some of their extinct predecessors. The paper ends with a short discussion on the language policy and practices of the institutions of the European Union. Europe lacks a language with the status and power comparable to Indonesian in Indonesia. The policy is therefore based on equal status of all national languages and on respect for all languages, including national minority ones. The practice, however, is unavoidably practical: